Optimasi Battery Charging pada Pendingin Minuman dengan Sumber Solar Cell untuk Beban Peltier Menggunakan Buckboost Converter - Hamzah Maulana Azhar (Journal of Applied Smart Electrical Network and Systems, 2021)
Currently, many electronic devices use the energy source from the solar cell which is stored in a battery. The battery is a portable, rechargeable power source. Solar energy is very suitable when converted to electrical energy because the amount of sunlight is infinite even though there is a period of time between sunrise and sunset. Converting solar energy to electrical energy requires a solar cell. One method that can be done is using the buck boost converter method with solar cell sources to create a battery charging control system. The Buck Boost Converter method was chosen because it can stabilize the output voltage from the solar cell when the weather is uncertain. If the light intensity of the sunlight is dim, the output voltage of the panel will also be low, then the converter will be in boost mode to increase the voltage level, on the other hand, if the light intensity of the panel output voltage will also be high, the converter will be in buck mode to lower the voltage level. The output voltage of this control system is maintained according to the battery charging voltage standard, which is 14 volts DC.